2017
DOI: 10.1007/978-3-319-70139-4_54
|View full text |Cite
|
Sign up to set email alerts
|

Position-Based Content Attention for Time Series Forecasting with Sequence-to-Sequence RNNs

Abstract: We propose here an extended attention model for sequence-to-sequence recurrent neural networks (RNNs) designed to capture (pseudo-)periods in time series. This extended attention model can be deployed on top of any RNN and is shown to yield state-of-the-art performance for time series forecasting on several univariate and multivariate time series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Although the BL learns separate dependencies along each mode, it is not obvious how a representation at a time instance interacts with other time instances or which time instances are important to the prediction at horizon T ′ . By incorporating the position information into the attention calculation scheme, the authors in [56] showed that the learned model only used a particular time instance in the past sequence to predict the future value at a given horizon for sequence-to-sequence learning. In order to learn the importance of each time instance in the proposed BL, we propose the Temporal Attention augmented Bilinear Layer (TABL) that maps the input X ∈ R D×T to the output Y ∈ R D ′ ×T ′ as follows:…”
Section: B Temporal Attention Augmented Bilinear Layermentioning
confidence: 99%
“…Although the BL learns separate dependencies along each mode, it is not obvious how a representation at a time instance interacts with other time instances or which time instances are important to the prediction at horizon T ′ . By incorporating the position information into the attention calculation scheme, the authors in [56] showed that the learned model only used a particular time instance in the past sequence to predict the future value at a given horizon for sequence-to-sequence learning. In order to learn the importance of each time instance in the proposed BL, we propose the Temporal Attention augmented Bilinear Layer (TABL) that maps the input X ∈ R D×T to the output Y ∈ R D ′ ×T ′ as follows:…”
Section: B Temporal Attention Augmented Bilinear Layermentioning
confidence: 99%
“…The attention mechanism is typically used in RNN architectures to improve the model performance. The works in [65][66][67] are a few examples where attention blocks were proposed and used with LSTM architectures for time series forecasting. Attention blocks have also been used with CNN architectures [40,43,68,69] for image classification and time series data.…”
Section: The Proposed Modelmentioning
confidence: 99%
“…Bianchi et al 2017compared different RNN variants and showed that LSTMs outperformed others on highly non-linear sequences with sharp spikes thanks to the quick memory cell modification mechanism. Cinar et al (2017) proposed using an LSTM encoder-decoder with position-based attention model to capture patterns of pseudo-periods in sequence data. They applied the attention mechanism (Bahdanau et al 2014) to explore similar local patterns in historical data for future prediction.…”
Section: Forecasting With Deep Learning Techniquesmentioning
confidence: 99%